Implementation of Project Based Learning in a Large Engineering Programme - Boland, Francis; Pavia, Sara; Mc Goldrick, Ciaran; Kelly, Kevin; Bennett, Gareth; O'Kelly, Kevin (My University, 2010)
The role of the engineer in industry has evolved, with today?s engineering businesses seeking engineers with abilities and attributes in two broad areas - technical understanding and enabling skills. Institutions within the engineering community such as Engineers Ireland, the Accreditation Board for Engineering and Technology, the Royal Academy of Engineering and members of the CDIO (Conceive Design, Implement, Operate) initiative have highlighted a need for new approaches to learning and teaching of engineering within our academic institutions. This paper reports on the recent implementation of project based design courses in both of the two engineering programmes offered by Trinity College Dublin. The projects are each carried out in small groups (typically four to six) and are virtually free of podium based teaching. Initially, the students are provided with a design brief, foundation level technical input and raw materials. The projects are developed around the principles of CDIO which represents best international practice for teaching design. The implementation of this methodology requires self-directed learning, teamwork and small group learning, culminating in the actual building and testing of a prototype. Some projects finish with a public competition which tends to generate huge excitement. The new courses have been seen to foster innovation and to provide a format that channels the student?s creative skills in a coherent and structured manner. The detail of the courses, the learning outcomes, and the resource overhead are presented as well as a discussion on the initial results from the programmes.
3rd International Symposium for Engineering Education (ISEE2010)
PUBLISHED
University College Cork
Keywords: engineering education; CDIO; Inclusive Society